Association Between Self-Perceived Stress and Cryptogenic Ischemic Stroke in Young Adults - Kutal, Shakar; Tulkki, Lauri Juhani; Sarkanen, Tomi; Redfors, Petra; Jood, Katarina; Nordanstig, Annika; Yeşilot, Nilüfer; Sezgin, Mine; Ylikotila, Pauli; Zedde, Marialuisa; Junttola, Ulla; Fromm, Annette; et al. (Ovid Technologies (Wolters Kluwer Health), 2025)
Background and objectives: Psychosocial stress is a potentially modifiable risk factor of early-onset ischemic stroke, with limited evidence suggesting a stronger association between stress and cryptogenic ischemic stroke (CIS) compared with strokes of known etiology. We aimed to explore the association between self-perceived stress and CIS, with subgroup analyses stratified by sex and age.
Methods: Young patients aged 18-49 years with a first-ever CIS and sex-matched and age-matched stroke-free controls from 19 European centers were included. Self-perceived stress was assessed using a modified version of the Perceived Stress Scale (PSS). Scores were categorized into low (0-13), moderate (14-26), and high (27-40) perceived stress. Conditional logistic regression-adjusted for age, level of education, traditional risk factors (hypertension, cardiovascular diseases, diabetes mellitus, heavy alcohol consumption, current smoking, obesity, diet, depression, and physical inactivity), and migraine with aura (MA)-was used to assess independent association between self-perceived stress and CIS.
Results: Altogether, 426 patients (median age 41 years; 47.7% women) and 426 controls were included. Patients were more often at least moderately stressed compared with controls (46.2% vs 33.3%, p < 0.001). In the entire study population, higher self-perceived stress as a discrete measure was independently associated with CIS: adjusted odds ratio (OR) 1.04 per point increase; 95% CI 1.01-1.07. Categorical PSS score analysis showed an independent association between moderate stress and CIS (OR 1.47; 95% CI 1.00-2.14), but not with high stress (2.62; 0.81-8.45). In sex-specific analysis, higher stress as a discrete measure was associated with CIS in women (1.06; 1.02-1.11), but not in men (1.02; 0.97-1.07). Moderate stress was associated with CIS in women (1.78; 1.07-2.96), but not in men (1.06; 0.58-1.96). When stratified by age, higher stress as a discrete measure was significantly associated with CIS only in patients aged 18-39 years (1.06; 1.00-1.11).
Discussion: Self-perceived stress was strongly correlated with an increased risk of early-onset CIS, even after robust adjustment for cardiovascular risk factors and MA. These findings highlight the need for further investigation into the mechanisms by which stress may contribute to the risk of CIS. Possibility of recall bias should be considered when interpreting the results.
Trial registration information: Clinical trial registration number: NCT01934725.